Downstream Effects of a Hydroelectric Reservoir on Aquatic Plant Assemblages. (2002) - Bernez, Ivan; Haury, Jacques; Ferreira, Maria Teresa
Abstract : Macrophytes were studied downstream of the Rophémel hydroelectric dam on the River Rance (Côtes d'Armor Department, western France) to assess the effects of hydroelectric functioning on river macrophyte communities. We studied ten representative sections of the hydro-peaking channel on five occasions in 1995 and 1996, on a 15-km stretch of river. Floristic surveys were carried out on sections 50 m in length, and genera of macroalgae, species of bryophyta, hydrophytes, and emergent rhizophytes were identified. For the aquatic bryophytes and spermatophytes section of our study, we compared our results with 19 th century floristic surveys, before the dam was built. During the vegetative growth period, the hydro-peaking frequency was low. The plant richness was highest near the dam. The macrophyte communities were highly modified according to the distance to the dam. The frequency and magnitude of hydro-peaking was related to the aquatic macrophyte richness in an Intermediate Disturbance Hypothesis position. However, the results of the eco-historical comparison with 19 th century floristic surveys point to the original nature of the flora found at the site. Some floral patterns, seen during both periods and at an interval of 133 years, were indicative of the ubiquity of the aquatic flora and of the plants' adaptability. This demonstrates the importance of taking river basin history into account in such biological surveys.